2022
DOI: 10.3389/fpubh.2022.822155
|View full text |Cite
|
Sign up to set email alerts
|

A School Intervention's Impact on Adolescents' Health-Related Knowledge and Behavior

Abstract: BackgroundMany factors can influence health behavior during adolescence, and the lifestyle of adolescents is associated with health behavior during adulthood. Therefore, their behavior can determine not only present, but also later health status.ObjectiveWe aimed to develop an intervention program to improve high school students' health behavior and to evaluate its effectiveness.MethodsWe performed our study at a secondary school in a rural town in East Hungary between 2016 and 2020. Sessions about healthy lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Young people obtain important information about health behaviours from their parents (Trucco et al, 2021 ) and teachers (Nagy-Pénzes et al, 2022 ). Consistent with previous research (AMA New South Wales, 2022 ; Brown et al, 2020 ; Patel et al, 2019 ; Pettigrew et al, 2022 ), we found that although school professionals held the most negative perceptions of e-cigarettes, the majority demonstrated a limited understanding of vaping and associated harms; and parents held the most positive perceptions, yet they too were mostly unaware of the health effects of vaping and the contents of vapes.…”
Section: Discussionmentioning
confidence: 99%
“…Young people obtain important information about health behaviours from their parents (Trucco et al, 2021 ) and teachers (Nagy-Pénzes et al, 2022 ). Consistent with previous research (AMA New South Wales, 2022 ; Brown et al, 2020 ; Patel et al, 2019 ; Pettigrew et al, 2022 ), we found that although school professionals held the most negative perceptions of e-cigarettes, the majority demonstrated a limited understanding of vaping and associated harms; and parents held the most positive perceptions, yet they too were mostly unaware of the health effects of vaping and the contents of vapes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Nagy-Pénzes et al ( 2022) focus on the information advancement on active lifestyle and put emphasis on the factor that the intervention approach was part of the school program, resulting into a positive impact as the students made progress on familiarity about healthrelated perception and attitude. Yet, it was emphasized that awareness must be accompanied by another possible factor to achieve behavioral modification (Nagy-Pénzes et al, 2022).…”
Section: Theme 2: Physical Literacy Focusmentioning
confidence: 99%
“…According to McQuinn et al, (2022) the school set up was considerably suitable for improving and managing students behavior towards being active. Children value their time on school therefore experience within the said place is crucial for their behavioral development (Nagy-Pénzes et al, 2022). Therefore, several studies were conducted regarding strategies on promoting physical activity, as well as evaluating the intervention program for sedentary lifestyle using school as its venue.…”
Section: Introductionmentioning
confidence: 99%
“…Many school-based interventions are effective in increasing physical activity and preventing obesity [25], [26]. In comparison, evidence on the effectiveness of school-based interventions targeting adolescents found that school-based interventions were twice as successful as interventions targeting adolescents in regular social settings [14], [25], [27]. The challenge of achieving health behavior change has prompted the exploration of new and interesting intervention strategies.…”
Section: Literatur Reviewmentioning
confidence: 99%